THEORETICAL-PRAGMATIC OVERVIEW OF LEARNING MOTIVATION - Ilona Sulichka (Педагогически форум)
The article discusses the motivation to learn as a part of the subject-subject pedagogical interaction. It is presented as an active multifaceted pedagogical, psycho-age and social problem. And also as a problem related to the overall development of school education. The problem of motivation in the school environment is considered theoretically. On this basis, references are made to the various practical situational models proposed in the scientific literature. Motivation is shaped as a specific problem area that is directly related to the school environment; the intellectual and cognitive development of the student; methodical and didactic skills of the teacher.